Trajetórias migrantes, trajetórias tecnológicas: experiências inclusivas em contextos de CTS no Brasil - Díaz Uzcategui, Francisco Javier (2025)
Historically, migration and technology are two permanent and decisive trajectories in human life. This research explores the horizon of migratory movements, presenting their levels, patterns, types, categories, and theoretical and empirical contexts around the world, in order to understand their complexity and historical background. Simultaneously, we review some perspectives on migration studies and contexts, emphasizing a panorama of contemporary migration in Brazil, with the arrival of people mainly from the Southern Hemisphere starting in 2000. Observing movements in recent years, we highlight the massive arrival of Haitians and, specifically, the Venezuelan diaspora. We underscore the importance of migrant social networks, understood as the relationships migrants establish before, during, and after their “multiterritorial” movements.In particular, this research studies some alternative proposals for the construction of participatory and inclusive technologies, specifically as proposals for political activism of resistance and democratic values of Participatory Design (PD), Social Technology (ST), and Technology for Social Inclusion (TSI), following historical and contemporary journeys in both the Global North and the Global South. This research also describes an experience with a digital repository of Open Educational Resources (OER), featuring written and multimedia didactic content for teaching and learning Portuguese for migrants in Brazil.This digital repository was created through participatory and dialogical approaches with outreach projects such as PBMIH from UFPR and PFOL from UTFPR, via an alliance based on political activism and the aforementioned values of PD and ST, adopted by these outreach projects to reach people and develop a project as a means of participation, inclusion, and sociotechnical alliance of actors internal and external to the university, in this case migrants and researchers.Finally, and based on the participatory experience of this repository, a comparative interpretation is made of some convergences and divergences between the approach of Participatory Design (PD) and the Latin American proposals in Social Technology (ST) and Technology for Social Inclusion (TSI), focusing on each of these approaches concerning aspects such as historically situated trajectory, ideal visions, sociotechnical alliances, political itineraries, sociotechnical systems, projections and artifacts, as well as their scope, contradictions, and challenges. These concepts allow us to understand the general contexts sought by these alternative proposals for technology construction, namely: collective control, inclusion, democracy, ideological struggle, and the pursuit of justice.